The study of consumer acceptance of catfish (pangasius hypophthalmus) ball which added with angkak as a colour additive - Loekman, Suardi; ', Hadriannisya; ', Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to evaluate the consumer aceptance on catfish balladded with angkak as a colour additive. Four types of catfish ball were preparedfrom a mixture of catfish meat, sago flour, tapioca flour, seaweed, egg, and spices(onion, white onion, pepper powder, salt); and each catfish ball was added withangkak at a level of 0%, 5%, 10% and 15%. Catfish balls were evaluated forconsumer acceptance, proximate composition and bacterial total. The resultshowed that the catfish ball added with 5% red rice flour was the best in quality.Protein, fat, carbohydrate, moisture, ash and bacterial total of the catfish ball was67.94%, 1.21 %, 0.42 %, 11.58% and 4.6 X 102 respectively.Keywords : angkak, catfish ball, additive